Neglected older women and men: Exploring age and gender as structural drivers of HIV among people aged over 60 in Uganda - Richards, Esther; Zalwango, Flavia; Seeley, Janet; Scholten, Francien; Theobald, Sally. (African Journal of AIDS Research, 2013)
This study explored how women’s and men’s gendered experiences from childhood to old age have shaped their vulnerability in relation to HIV both in terms of their individual risk of HIV and their access to and experiences of HIV services. It was a small scale-scale study conducted in urban and rural sites in Uganda between October 2011 and March 2012. The study used qualitative methods: in-depth interviews (with 31 participants) and focus group discussions (FGDs) with older women (2) and men (2) in urban and rural sites and 7 key informant interviews (KIIs) with stakeholders from government and non-government agencies working on HIV issues. Women’s position, the cultural management of sex and gender and contextual stigma related to HIV and to old age inter-relate to produce particular areas of vulnerability to the HIV epidemic among older women and men. Women report the compounding factor of gender-based violence marking many of their sexual relationships throughout their lives, including in older age. Both women and men report extremely fragile livelihoods in their old age. Older people are exposed to HIV through multiple and intersecting drivers of risk and represent an often neglected population within health systems. Research and interventions need to go beyond only conceptualising older people as ‘carers’ to better address their gendered vulnerabilities to HIV in relation to all aspects of policy and programming.
Keywords: older people; Uganda; HIV; gender; age; structural drivers